Penerapan Metode Sosio Drama untuk Meningkatkan Hasil Belajar PKn pada Materi Sistem dan Dinamika Demokrasi Pancasila Siswa Kelas XI-MIA 1 SMA - Sugianto, Sugianto (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study aims to determine the application of the Socio Drama Method to Improving Civics Learning Outcomes in the System and Dynamics of Pancasila Democracy Material for Class XI-MIA 1 Odd Semester Students of SMA Negeri 1 Sekotong in the 2017/2018 Academic Year. This type of research is Classroom Action Research (CAR). The subjects in this study were 20 students who had problems in Civics lessons whose learning outcomes did not meet the minimum completeness criteria (KKM) taken from class XI-MIA 1. The object involved in this study was Civics learning outcomes. After the data is collected, then analyzed with quantitative descriptive analysis. The results of the data analysis showed that the average increase in Civics learning outcomes from pre-cycle to cycle I was 2.03 points, pre-cycle to cycle II was 12.53 points, and cycle I to cycle II was 10.50 points. Based on the results of the data analysis, it can be concluded that the application of the socio-drama method can improve Civics learning outcomes in the System and Dynamics of Pancasila Democracy Material for Class XI-MIA 1 Odd Semester Students of SMA Negeri 1 Sekotong for the 2017/2018 Academic Year.